Physical Therapy's Effectiveness In Treating Typical Sports Injuries (Journal of Namibian Studies : History Politics Culture, 2022)
Physical therapy provides a thorough approach to treatment that tackles pain, dysfunction, and impairment, making it an essential component in the care of common sports injuries. This study examines the effectiveness of physical therapy interventions in the management of common sports injuries, such as ligament injuries, tendinitis, sprains, and strains. The usefulness of different physical therapy modalities, such as exercise prescription, manual therapy techniques, modalities for pain management, and functional rehabilitation, is assessed by a study of the literature and clinical studies that have already been conducted. The results emphasize the value of early intervention, customized treatment regimens, and all- encompassing rehabilitation techniques in maximizing results and enabling a risk-free return to competition for athletes at all levels.